Foundations in strategic management - Harrison, Jeffrey S.
FOUNDATIONS IN STRATEGIC MANAGEMENT, 4E, embraces recent business changes by now including strategizing in the global arena, the challenges of the increased globalization, and a more dedicated coverage of ethics along with the more traditional teachings. Although much more concise than its competitors, it remains a well-rounded and indispensable source covering the foundations of strategic management